A highly sensitive, non-radioactive assay for T cell activation in cattle: Applications in screening for antigens recognised by CD4+ and CD8+ T cells - Ballingall, Keith T.; Mwangi, David Miano; MacHugh, Niall D.; Taracha, E.L.N.; Totte, P.; McKeever, Declan J. (Elsevier, 2000)
We describe a highly sensitive, non-radioactive assay for T cell activation, based on the rapid induction of class II MHC expression by constitutively negative bovine endothelial cells, when cultured in the presence of supernatants derived from activated bovine T cells. We demonstrate the effectiveness of this assay in detecting rBoIFN y and activation of immune CD4 - and CD8 - T cell lines and clones in response to specific antigen and transfected COS-7 cells, respectively. We also demonstrate its utility in identifying purified pathogen fractions that activate immune CD4-T cell clones.